2017
DOI: 10.1002/ls.1378
|View full text |Cite
|
Sign up to set email alerts
|

The effect solid particle lubricant contamination on the dynamic behavior of compliant journal bearings

Abstract: The proposed work concerns a theoretical and numerical investigation of the effect of solid particle contamination of lubricant oils on the static and dynamic characteristics of a finite length compliant journal bearing operating under isothermal conditions with laminar flow. In the present investigation, we use simple models based on the Einstein's mixture theory, which is characterized by the presence of suspended rigid particles in a fluid. Using the classical assumptions of lubrication, a Reynolds equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Solid particles of various sizes and shapes are inducted into lubricant as a) debris during maintenance, b) dust or soot from the environment, and c) metal particles due to wear mechanism. Solid particle contamination in a journal bearing has been investigated by Boucherit et al [13]. It is understood from their study that solid particle contamination has a substantial impact on friction, surface deformation, and flow rate of the lubricant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid particles of various sizes and shapes are inducted into lubricant as a) debris during maintenance, b) dust or soot from the environment, and c) metal particles due to wear mechanism. Solid particle contamination in a journal bearing has been investigated by Boucherit et al [13]. It is understood from their study that solid particle contamination has a substantial impact on friction, surface deformation, and flow rate of the lubricant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The size of the SiC particles considered in this study is 10 microns. The particle size considered in this study is based on the investigation made by Boucherit et al [13]. It was found that the particle average size of 75 microns influences the wear over the gear tooth surface.…”
Section: Lubricant Conditionsmentioning
confidence: 99%
“…In recent years, some studies have pointed out that particles significantly affect the friction properties of the three-body contact interface, especially in high-speed and precision machinery. Studies in this field are mainly on the effects of properties of solid particles on the rheology of lubricants, 4,5 three-body microcontact modeling, 6,7 effects of solid particle and rheological properties on bearing static and dynamic characteristics, 8,9 _ENREF_8 and experimental studies on solid particles. 10,11 Mixed EHL is a typical characteristic of lubricated machine elements in nonconformal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the Reynolds equation is discretized by finite difference method and solved by Iterative solution method. In actual calculation, due to the nonlinear nature of the equation, the calculation results may not stable enough, and even not converge [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%